(untitled) - Kirkpatrick, Betty (Singapore, 2005)
This is the second of two books that are aimed at developing students' skills in vocabulary building, and in reading and understanding information texts. The 26 passages in each book cover a wide range of high interset topic. In reading the passages and working through the comprehension and discussion questions, students will broaden their understanding of the social and contemporary issues discussed
Keywords: Vocabulary,Comprehension,Từ vựng,Thuật ngữ; Building,Xây dựng